2021
DOI: 10.1128/jcm.00745-20
|View full text |Cite|
|
Sign up to set email alerts
|

SHERLOCK and DETECTR: CRISPR-Cas Systems as Potential Rapid Diagnostic Tools for Emerging Infectious Diseases

Abstract: Infectious diseases are one of the most intimidating threats to human race, responsible for an immense burden of disabilities and deaths. Rapid diagnosis and treatment of infectious diseases is a better understanding of its pathogenesis. According to WHO, the ideal approach for detecting foreign pathogens should be rapid, specific, sensitive, instrument-free and cost-effective. Nucleic acid pathogen detection methods, typically PCR have numerous limitations, such as highly sophisticated equipments, reagents, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(114 citation statements)
references
References 73 publications
(117 reference statements)
0
113
0
1
Order By: Relevance
“…Cas13 and Cas12a are activated upon binding to target nucleic acids, RNA and DNA, respectively, where they excise reporter RNA sequences and cut a quenched fluorescent probe to generate a fluorescence signal (187)(188)(189). Both tests are low-cost, can be performed in 1 h (188,190,191), and have been granted U.S. FDA EUA status (72,192,193). The SHERLOCK test demonstrated a sensitivity of 93.1% and a specificity of 98.5% (191), while the DETECTR assay demonstrated 95% positive predictive agreement and 100% negative predictive agreement (188), which makes both strong rapid diagnostic candidates.…”
Section: Other Methods Of Viral Rna Detectionmentioning
confidence: 99%
“…Cas13 and Cas12a are activated upon binding to target nucleic acids, RNA and DNA, respectively, where they excise reporter RNA sequences and cut a quenched fluorescent probe to generate a fluorescence signal (187)(188)(189). Both tests are low-cost, can be performed in 1 h (188,190,191), and have been granted U.S. FDA EUA status (72,192,193). The SHERLOCK test demonstrated a sensitivity of 93.1% and a specificity of 98.5% (191), while the DETECTR assay demonstrated 95% positive predictive agreement and 100% negative predictive agreement (188), which makes both strong rapid diagnostic candidates.…”
Section: Other Methods Of Viral Rna Detectionmentioning
confidence: 99%
“…However, studies have shown specificity between 71.4% and 98.5% for CRISPR, 78 , 79 so further evaluations are required since a recent review has concluded that although CRISPR technology is still in its infancy it is potentially revolutionary as tests are rapid and portable. 80 …”
Section: Other Novel Emerging Technologiesmentioning
confidence: 99%
“…A growing number of preclinical studies based on rodent and other animal models indicate that CRISPR-Cas systems have the potential for therapeutic usage in different diseases, including genetic diseases, 31 infectious diseases, 32 cancers, 7 , 33 immunological diseases (autoimmunity and immunodeficiency), 34 etc.…”
Section: Preclinical Testsmentioning
confidence: 99%